Accretion and photodesorption of CO ice as a function of the incident angle of deposition. Issue 4 (2nd May 2019) - González Díaz, C; Carrascosa de Lucas, H; Aparicio, S; Muñoz Caro, G M; Sie, N-E; Hsiao, L-C; Cazaux, S; Chen, Y-J
ABSTRACT: Non-thermal desorption of interstellar and circumstellar ice mantles on dust grains, in particular ultraviolet photon-induced desorption, has gained importance in recent years. These processes may account for the observed gas phase abundances of molecules like CO toward cold interstellar clouds. Ice mantle growth results from gas molecules impinging on the dust from all directions and incidence angles. Nevertheless, the effect of the incident angle for deposition on ice photodesorption rate has not been studied. This work explores the impact on the accretion and photodesorption rates of the incidence angle of CO gas molecules with the cold surface during deposition of a CO ice layer. Infrared spectroscopy monitored CO ice upon deposition at different angles, ultraviolet irradiation, and subsequent warm-up. Vacuum ultraviolet spectroscopy and a Ni-mesh measured the emission of the ultraviolet lamp. Molecules ejected from the ice to the gas during irradiation or warm-up were characterized by a quadrupole mass spectrometer. The photodesorption rate of CO ice deposited at 11 K and different incident angles were rather stable between 0° and 45°. A maximum in the CO photodesorption rate appeared around 70° incidence deposition angle. The same deposition angle leads to the maximum surface area of water ice. Although this study of the surface area could not be performed for CO ice, the similar angle dependence in the photodesorption and the ice surface area suggests that they are closely related. Further evidence for a dependence of CO ice morphology on deposition angle is provided by thermal desorption of CO ice experiments.